"UNITED WINDOW" LLC ways to improve the marketing activities of the production enterprise - Musayeva Shoira Azimovna (Journal of Artificial Intelligence and Digital Economy, 2024)
In this article, we will study the demand for products and services, analyze competitors, determine the needs of potential customers and market requirements, develop a marketing strategy: determine product assortment and prices, focus on specific areas, establish product distribution channels. , development of marketing messages, promotions, customer incentives, participation in exhibitions and events are considered..